KUALITAS PELAYANAN AKTA KELAHIRAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BANJAR TAHUN 2019 - Siti Maisyarah (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2019)
The research objectives were to (1) find out the quality of service of birth certificates and (2) to find out the factors that hindered birth certificate services at the Banjar Regency Population and Civil Registration Service. The research method uses a qualitative approach with descriptive research. Data was collected by observation, interview, and documentation techniques, to Mitryadi, an employee of the Banjar Regency Population and Registrar's Office and a number of community service users. Samples were determined using purposive sampling and snowball sampling techniques. Data analysis uses interactive analysis techniques that have 3 steps consisting of data reduction, data presentation, and conclusion drawing. The results of the study show that (1) Quality of Service of Birth Certificates at the Department of Population and Civil Registration of Banjar Regency has implemented the Tangible, Reliability, Responsiveness, Assurance, and Empathy dimensions. However, there are several indicators that do not work in accordance with service standards, such as inconvenience in service areas, incomplete infrastructure, and lack of friendliness in the service process. (2) Inhibiting factors for birth certificate services at the Department of Population and Civil Registration of Kabupaten Banjar are infrastructure facilities that have not been optimal, there is still a lack of waiting chairs and tables, a narrow service room, the absence of large generators and network disturbances.